Pangestoh as an Expression of Commitment: A Review of Citizens' Participation and Involvement at the Salafiyah Raudlatul Ulum Islamic Boarding School - Fauzan, Fauzan; Taufik, Taufik Al Amin (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2024)
The Raudlatul Ulum Salafiyah Islamic Boarding School plays a crucial role in shaping character, morality, and religious identity through the value of Pangestoh, an expression of commitment and values manifested in various activities and community involvement. Despite its importance, there has been limited research on Pangestoh. This study aims to explore the implementation of Pangestoh, its role in community participation, and its impact on the social life and independence of students. This qualitative research employs a phenomenological approach, focusing on the Raudlatul Ulum Salafiyah Islamic Boarding School in Sumberwringin, Jember Regency. Data collection methods include observation, interviews, and documentation. Data analysis involves describing the general meaning of participants' experiences related to Pangestoh. The findings reveal that Pangestoh is integral to the spiritual and social life of the boarding school, emphasizing mutual trust, loyalty, and active community involvement. It significantly shapes the students' character and supports the institution's goal of spreading Islamic teachings and fostering a sense of solidarity and mutual support. Pangestoh, as a commitment value, is vital in developing the student's character and the institution's effectiveness. Understanding its influence on social life and independence provides insights for curriculum development, ensuring Pangestoh values are more integrated into the educational process, ultimately enhancing the overall educational experience and community cohesion at Islamic boarding schools.